CALCISPONGIA FROM THE MIDDLE AND UPPER JURASSIC OF THE SHOTORI MOUNTAINS, NORTHEAST IRAN.PART I. MAMMILLOPORA BRONN, TREMOSPONGIA D´ORBIGNY, STELLISPONGIA GOLDFUSS, ENAULOFUNGIA FROMENTEL, AND DEHUKIA N. GEN. - BABA SENOWBARI-DARYAN; FRANZ T. FÜRSICH; KOOROSH RASHIDI (Rivista Italiana di Paleontologia e Stratigrafia, 2011)
Middle to Upper Jurassic shelf lagoon, platform, and slope deposits, called the Esfandiar Limestone Formation and Qal-eh Dokhtar Formation, respectively, are widespread in the Shotori Mountains of east-central Iran. Although small in-situ patch reefs are known only from the shelf lagoon, reef organisms (corals, sponges) are common as allochthonous components in slope deposits of the Qal-eh Dokhtar Formation and in proximal basinal silty marls of the Korond Formation. Here, some massive calcisponges, including the new genus Dehukia, are described comprising the taxa Mammillopora iranica n. sp., Mammillopora polyosculata n. sp., Tremospongia pulvinaria (Goldfuss), Tremospongia pellisfera n. sp., Dehukia maxima n. sp., Dehukia raisossadati, Dehukia media n. sp., Stellispongia stellata (Goldfuss), and Enaulofungia globosa n. sp.